2018
DOI: 10.22610/jebs.v10i1(j).2084
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape: The Influence of Packaging on South African BOP Consumers' Decision-Making

Abstract: The bottom of the pyramid (BOP) proposition espouses the use of ‘single-serve’ or ‘sachet’ packaging in order to enhance affordability, encourage consumption and offer an assortment of good-quality products to BOP consumers. This study assesses the influence of packaging (in relation to size and price of different quantities) on South African BOP consumers’ purchase decisions. The study analyses whether or not these consumers have a tendency to purchase smaller quantities of products as opposed to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Research conducted by [21] showed the visual stimuli as the most influencing packaging element. This study had selected 103 low-income group consumers [22] conducted a study on 600 rural South-African BoP consumers and showed that there is a tendency of buying products with larger packets, reusable containers, and packets. [23] discussed the importance of packaging elements in case of adopting new innovative products in the BoP markets.…”
Section: The Bop Marketmentioning
confidence: 99%
“…Research conducted by [21] showed the visual stimuli as the most influencing packaging element. This study had selected 103 low-income group consumers [22] conducted a study on 600 rural South-African BoP consumers and showed that there is a tendency of buying products with larger packets, reusable containers, and packets. [23] discussed the importance of packaging elements in case of adopting new innovative products in the BoP markets.…”
Section: The Bop Marketmentioning
confidence: 99%